Use of Information and Communication Technologies and Health Behaviours in Elite Combat Sport Athletes (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
Background and Aim. The rapid integration of Information and Communication Technologies (ICT) and wearable sensors have transformed elite sports management. However, the impact of multi-dimensional ICT engagement on the unique psychophysiological ecosystem of elite combat athletes remains under-researched. This study aims to investigate the association between ICT usage patterns and interconnected health behaviours, specifically focusing on sleep quality, pre-competition stress, and nutritional adherence during weight-cutting phases.Methods. This cross-sectional study investigated 65 elite combat athletes (N = 65; 76.9% male, 23.1% female), predominantly international-level competitors (86.2%) across different disciplines. The cohort had a mean age of 26.8 ± 4.4 years and 9.2 ± 3.8 years of elite experience. Data were collected through structured, self-administered digital questionnaires of four validated scales: IPAQ-SF (physical activity), PSQI (sleep), PSS-10 (stress), and REAP-S (nutrition), integrated with a Composite ICT Engagement Index (CIEI).Results. Statistical analysis revealed a moderate positive correlation between pre-competition weigh-in stress and sleep difficulty (rₛ = .370, p < .01), while the PSS-10 scale showed high internal consistency (α = .783). Furthermore, high CIEI scores were significantly associated with frequent digital nutrition tracking (p < .05) and elevated perceived application pressure (rₛ = .516, p < .001). Additionally, bedtime screen time was found to correlate with post-competition binge eating behaviour (rₛ = .370, p = .002), and the frequency of vigorous physical activity was strongly linked to nocturnal awakenings (rₛ = .436, p < .009).Conclusions. Digital tools provide essential nutritional structure but simultaneously trigger a monitoring paradox that disrupts sleep in elite combat athletes. Findings suggest that excessive ICT reliance may impair recovery by intensifying application-related pressure and exacerbating weight-cut-induced stress.Keywords: Combat sports; sleep quality; pre-competition stress; wearable technology; digital health engagement